Impacts of COVID-19 on HIV/AIDS-Related Services in California - Kimberly A. Koester PhD; Shannon M. Fuller MS; Wayne T. Steward MPH, PhD; Emily A. Arnold MPH, PhD (Journal of the International Association of Providers of AIDS Care, 2022)
The degree to which COVID-19 has disrupted the advances in reducing new HIV infections and preventing AIDS-related deaths is unknown. We present findings related to the effect COVID-19 had on HIV, sexual health and harm reduction service delivery in the state of California. We conducted a qualitative rapid assessment with health care providers, as well as representatives from non-medical support service agencies serving clients living with HIV in a range of counties in California. Some organizations adapted fairly easily while others struggled or were unable to adapt at all. Clinics were better positioned than community-based organizations to accommodate COVID restrictions and to quickly reestablish services. Influential forces that softened or calcified the hardships created by COVID-19 included influx of funding, flexibility in managing funds, networking and relationships, and workforce vulnerabilities. These data clearly suggest that an enhanced level of flexibility within funding streams and reporting requirements should be continued .